Kampanye Sosial Stop Stigma Lesbian, Gay, Biseksual, Dan Transgender (LGBT) Terhadap Wanita Maskulin Di Kota Palembang - Fatwani Felanty; Bobby Halim; Mukshin Patriansah (VisArt: Jurnal Seni Rupa dan Design, 2024)
Stigma refers to a negative view or attitude towards the mental, physical, or social aspects of an individual or group, reflecting social disapproval. The presence of the Lesbian, Gay, Bisexual, dan Transgender (LGBT) community with non-normative behavior or appearance often triggers stigma and negative labels, even though the individual does not behave deviantly. The main issue at issue is the assumption that women with a 'tomboy' or masculine appearance are synonymous with lesbian sexual orientation, which is not always true. This research aims to explore the impact of the formation of these views on individuals who experience stigma, as well as efforts to reduce stereotypes in Palembang City. The design method used is the design thinking method applied in various media such as pre-media, main media, and follow-up media. Data collection techniques through observation, questionnaires, interviews, literature and websites. This research will produce various media including posters, t-shirts, tote bags, mirror reflections, Instagram feeds, calendars, pins, key chains, refrigerator magnets, narrative videos and photo stories. It is hoped that the achievements and targets of this design will be able to become informative media that will change the negative stigma of the people of Palembang towards masculine women.